Penerapan Media Job Sheet Untuk Meningkatkan Hasil Belajar pada Praktik Pola Kemeja Pria di MAN 2 Madiun - Turahim, Zahra Rahma; Marniati Marniati (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study was motivated by the low learning outcomes of students in making men’s shirt patterns, which had not met the minimum achievement criterion of 74. The initial average score was 72 with only 30% mastery. This study aimed to improve learning outcomes through the use of job sheet media. The research employed classroom action research conducted in two cycles, including planning, action, observation, and reflection. This study was conducted at MAN 2 Madiun with 15 eleventh-grade students as the research subjects. Data were collected through tests, and analyzed using descriptive quantitative techniques. The results show an increase in the average score to 79 with 80% mastery in the first cycle, and 86.3 with 100% mastery in the second cycle. Therefore, job sheet media is effective in improving students’ learning outcomes.